2019
DOI: 10.2147/prom.s232166
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Adolescent Patient Experiences of Diabetes Care Questionnaire (APEQ-DC): Reliability and Validity in a Study Based on Data from the Norwegian Childhood Diabetes Registry</p>

Abstract: PurposePatient-reported experiences are a key source of information on quality in health care. Most patient experience surveys only include adults’ assessments including parent or proxy surveys in child health care settings. The aim of this study was to determine the psychometric properties of the Adolescent Patient Experiences of Diabetes Care Questionnaire, a new instrument developed to measure adolescent experiences of paediatric diabetes care at hospital outpatient departments in Norway.Patients and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The results are consistent with a number of previous studies reporting that mail surveys achieve higher response rates than electronic and web-based approaches. [2][3][4][5][6][7][8][9][10][11] A recent Consumer Assessment of Healthcare Providers and Systems survey produced similar results when comparing protocols based on web responses via an email invitation and mail. 7 The mail protocol yielded more than twice the response rate of the web approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are consistent with a number of previous studies reporting that mail surveys achieve higher response rates than electronic and web-based approaches. [2][3][4][5][6][7][8][9][10][11] A recent Consumer Assessment of Healthcare Providers and Systems survey produced similar results when comparing protocols based on web responses via an email invitation and mail. 7 The mail protocol yielded more than twice the response rate of the web approach.…”
Section: Discussionmentioning
confidence: 99%
“…Open access indicate that web mode surveys have lower response rates than other modes. [2][3][4][5][6][7][8][9][10][11] In the national patient experience survey among patients visiting GPs in 2014 in Norway, only 18% of respondents answered electronically. 4 However, the potential advantages of lower costs and shorter data-collection periods are important arguments for performing further research into web-based surveys.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding authors of all 27 studies were contacted; 21 authors replied. From these, 15 of the 21 studies confirmed they included a YPAG [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] ; the remaining 6 either did not use a YPAG (n=3) [28][29][30] or had YPAG members who were all aged over 18 years (n=3). 31,32,33 For the six studies where authors did not respond, we assumed a YPAG was used based on information provided in the paper.…”
Section: Identifying and Quantifying Ypag Reportingmentioning
confidence: 99%
“…The identified studies that used a YPAG covered a range of topics such as cyberbullying, 14 supporting young people in their decision to join a clinical trial, 24 sexual health, 18,22,25 exploring novel mental health treatment options, 13,20 healthy eating interventions, 26 and treatment for conditions such as arthritis 15 and diabetes. 27 All but two of the studies were conducted in high income countries. 25,38 In terms of level and type of involvement, YPAG contribution was identified across all different phases of the research process, but most commonly in the research design phase (Figure 2).…”
Section: Characterising Ypag Use In Researchmentioning
confidence: 99%
“…Most of the items on experience were scored on a 5-point response scale ranging from 1 ("not at all") to 5 ("to a very large extent"). The 5-point response scale was chosen by the NIPH to be consistently applied in the surveys, making it possible to compare over time, and to some extent between different healthcare user groups [7,9,[12][13][14]. Most questionnaires addressing patient experiences have used items with scales where each point has a descriptor [15].…”
Section: Questionnaire Development and Contentmentioning
confidence: 99%